2012
DOI: 10.1016/j.mayocp.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of Epidemiological Findings and Public Health Decisions: An Illustration From the Rochester Epidemiology Project

Abstract: Objective: To illustrate the problem of generalizability of epidemiological findings derived from a single population using data from the Rochester Epidemiology Project and from the US Census. Methods: We compared the characteristics of the Olmsted County, Minnesota, population with the characteristics of populations residing in the state of Minnesota, the Upper Midwest, and the entire United States. Results: Age, sex, and ethnic characteristics of Olmsted County were similar to those of the state of Minnesota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
594
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 583 publications
(610 citation statements)
references
References 27 publications
14
594
2
Order By: Relevance
“…A study comparing the characteristics of the Olmsted County, Minnesota population with the characteristics of other populations revealed that age, sex, and ethnic characteristics of Olmsted County were similar to those of the state of Minnesota and the Upper Midwest from 1970 to 2000. However, Olmsted County was less ethnically diverse than the entire U.S. population (15). Thus, it is possible that the relationship of the mechanism of detection and the incidence of thyroid cancer varies depending on the source of data; however, the similarities between our thyroid cancer incidence rate in 2000-2012 and the nationally representative SEER cancer incidence rate incidence rate in 2009 suggest that the variation may be minimal.…”
Section: Limitations and Strengthsmentioning
confidence: 81%
“…A study comparing the characteristics of the Olmsted County, Minnesota population with the characteristics of other populations revealed that age, sex, and ethnic characteristics of Olmsted County were similar to those of the state of Minnesota and the Upper Midwest from 1970 to 2000. However, Olmsted County was less ethnically diverse than the entire U.S. population (15). Thus, it is possible that the relationship of the mechanism of detection and the incidence of thyroid cancer varies depending on the source of data; however, the similarities between our thyroid cancer incidence rate in 2000-2012 and the nationally representative SEER cancer incidence rate incidence rate in 2009 suggest that the variation may be minimal.…”
Section: Limitations and Strengthsmentioning
confidence: 81%
“…Another limitation is the limited diversity of those living in Olmsted County, a population that is mostly non‐Hispanic white. However, the epidemiological characteristics of Olmsted County for age, sex, morbidity, and mortality are comparable to those of the state of Minnesota and the entire United States 40. Last, misclassification bias could potentially affect our sample; our estimates are based on a single measure of body composition as the exposure variable, assuming that body composition will not change through follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding relative mortality data post-total hip and knee replacement, our estimates are almost identical to patterns observed for other large cohorts or national data. Although the local population is less ethnically diverse than the entire U.S. population, mortality rates are similar 25,26 . Similarly, the contralateral procedure estimates are consistent with those in the published literature 27 .…”
mentioning
confidence: 99%